(untitled) (Research, Society and Development, 2020)
Polysaccharides are a sustainable material for coatings and edible films, as they are nontoxic, widely available in nature and have selective permeability to CO2 and O2. In this work, a laboratory research on a quali/quantitative basis, sodium alginate films were developed, with and without post-film cross-linking, as well as chitosan films incorporating Z. officinale extract as an antimicrobial additive. Several properties such as solubility, moisture content, swelling, morphology and antimicrobial activity of prepared films were compared. The alginate films with crosslinking and incorporation of extract of Z. officinale showed the best characteristics to be used as medicated dressing, since it presents low solubility in water, higher swelling, and lower moisture content. In addition, the alginate film with crosslinking and incorporation of medium concentration of Z. officinale extract showed antimicrobial activity against Bacillus cereus.